Determinants Of Profit Shifting Decision: Analysis Of Multinational Companies In Indonesia - Hargiasto, Hartito; Mardiana, Karlin Sagita; Prasetyaningrum, Oktavia Rizki; Firmansyah, Amrie (Educoretax, 2024)
Taxpayers typically seek to decrease their tax burden through tax avoidance or planning. Multinational corporations have the opportunity to dodge taxes due to their international operations. The most popular form of tax avoidance for multinational corporations is to move income to subsidiaries in low-tax nations. This study investigates the factors that influence profit-shifting decisions by multinational corporations operating in Indonesia, such as tax rate differential, multinationality, firm size, and use of tax havens. This study employs secondary data from financial statements of firms listed on The Multinational Enterprise Information Platform database, which is the outcome of OECD and UNSD collaboration for 2022 as of January 2024 at https://www.oecd.org/sdd/its/mne-platform. The purposive sampling yielded 148 observations. Multiple linear regression analysis was used to process cross-sectional research data. According to this study, disparities in tax rates and firm size have a favorable effect on profit-shifting decisions. However, multinationality and presence in a tax haven country do not impact profit-shifting decisions. The results of this research can be used by tax authorities in Indonesia to consider when establishing rules that can prevent shifts in the earnings of multinational corporations with the goal of tax avoidance.